PCR based detection of tcdCΔ117 in Clostridium difficile infection identifies patients at risk for recurrence – A hospital-based prospective observational study. (June 2019) - Jazmati, N.; Hain, O.; Hellmich, M.; Plum, G.; Kaasch, A.
Abstract: Objectives: Increasing incidence and severity of Clostridium difficile infection (CDI) in the last decades has been attributed to the emergence of hypervirulent C. difficile strain PCR-ribotype 027 (RT027). Commercial multiplex real-time PCR tests allow the presumptive identification of RT027 by detecting a single-base deletion at nt117 in the tcdC gene ( tcdC Δ117). The clinical usefulness of the detection of tcdC Δ117 is unclear. Therefore, we evaluated test performance and clinical association of the detection of tcdC Δ117 in patients with CDI in a prospective observational study conducted in a tertiary care hospital in Germany. Methods: From June to October 2015, stool from all patients with suspected CDI was tested for C. difficile according to ESCMID guidelines. C. difficile was cultured from positive samples and ribotyping was performed. Clinical data were collected prospectively from all C. difficile positive patients. Results: From 1121 tested stool samples 107 patients with CDI were included in the study. TcdC Δ117 was detected in 18 (16.8%) of these patients. Multivariable logistic regression analysis revealed an independent association of detection of tcdC Δ117 with a further episode of CDI (OR 14.6; 95% CI 3.6–58.3; p < 0.001) and death within 30 days of the positive test (OR 5.1; 95% CI 1.0–25.7; p = 0.046). As follow up data are limited, it remains unclear, whether the further episode of CDI was due to tcdC Δ117 (recurrence) or another type. Conclusion: In our setting, PCR-based detection of tcdC Δ117 identified patients at risk for recurrent CDI and increased mortality and thus may guide therapeutic choices in CDI patients at the time of diagnosis. Highlights: Detection of tcdC Δ117 predicts recurrent C. difficile infection (CDI). Detection of tcdCΔ117 is associated with higher overall mortality in CDI patients. Detection of tcdC Δ117 is not associated with severe or severe complicated CDI. Detection of tcdC Δ117 is highly correlated to detection of RT027 by PCR-ribotyping.